2022
DOI: 10.1029/2022jb024040
|View full text |Cite
|
Sign up to set email alerts
|

Geysers, Boiling Groundwater and Tectonics: The 3D Subsurface Resistive Structure of the Haukadalur Hydrothermal Field, Iceland

Abstract: 3D resistive structure of the geyser-hosting Haukadalur hydrothermal field;• Vapour-saturated boiling reservoirs feeding geysers and hydrothermal ponds;• Fluid flow controlled by local tectonics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The temperature drop during the conduit cooling phase is associated with mass transfer: (a) evacuation of water and vapor associated with the eruption and (b) filling of the conduit by phreatic water through fractures and water cooled in the jet falling back in the vent (Eibl et al., 2021). This results in a more dramatic temperature decay at depth with respect to the shallow conduit, because of the water temperature gradient in the conduit and the more uniform temperature of phreatic water (Lupi et al., 2022). In parallel, duration of the conduit cooling phase decreases with depth.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The temperature drop during the conduit cooling phase is associated with mass transfer: (a) evacuation of water and vapor associated with the eruption and (b) filling of the conduit by phreatic water through fractures and water cooled in the jet falling back in the vent (Eibl et al., 2021). This results in a more dramatic temperature decay at depth with respect to the shallow conduit, because of the water temperature gradient in the conduit and the more uniform temperature of phreatic water (Lupi et al., 2022). In parallel, duration of the conduit cooling phase decreases with depth.…”
Section: Discussionmentioning
confidence: 99%
“…No cross‐correlation between Great Geysir and Strokkur temperature signals could be established. A recent geo‐electric survey suggested that both geysers would be connected at depth to a same reservoir by a network of fault and fractures (Lupi et al., 2022). However, deep signals are likely modulated by the complex geometry of this connection, hampering any synchronicity in the temperature records.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations